Pengembangan Instrumen Penilaian Autentik Kurikulum 2013 Aspek Afektif dalam Mata Pelajaran PAI Kelas VII di SMPN 3 Kalasan - Jatmiko, Anggi (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2018)
This research is motivated by the implementation of curriculum 13 in the teaching and learning process which requires teachers to be able to provide assessments to students according to the provisions of the curriculum. In addition, the assessment must be comprehensive using a variety of methods and tools to assess the various competencies or abilities of students, so that the overall ability profile of students is drawn. The problem here is what is the process of developing the assessment instrument and what is its feasibility. This research is a development research or what is often called R & D (Research and Development) which takes the background at SMPN 3 Kalasan. Data collection was carried out by interviewing, documenting, observing, and using a questionnaire. The research carried out was to develop an authentic assessment instrument for the attitude or affective domain and test the appropriateness of the instrument. The data analysis was carried out by examining the assessment instruments that had been made previously and had also been tested on students. Data analysis was performed using the SPSS statistical program. The data obtained from the results of the SPSS analysis can then be used as an assessment of the level of validity and reliability of the assessment instrument. The results showed: (1) The process of developing an authentic 2013 curriculum assessment instrument for the affective aspects of Islamic Education at SMP class VII started from analyzing potential problems and data collection which then carried out product design, validation and design revisions so that the product could be tested and analyzed and revised for can be used as a final product that is ready to be produced and used. (2) The results of the analysis of the validity test show 97.5% of valid statement items or 39 statements out of a total of 40 can be declared feasible, while for the reliability results obtained a reliability coefficient of 0.892, thus, the assessment instrument that has been made is reliable because the value of the reliability coefficient is more. the size of the r-level table is 5% (0.195) or 1% (0.256), according to the reliability interpretation table, the reliability criteria can be said to be very high, as well as the assessment results show the feasibility level of 82.8% or when viewed from the feasibility table that has been made can be said to be worthy. Keywords: Authentic Assessment, 2013 Curriculum, PAI Subject